Evaluation of sustainable groundwater extraction for water intake using visual modflow at Tanjung Mas - Mhd Ramzam, Muhammad Aidil Hakim (2020)
Groundwater is the largest available reservoir of freshwater in the world with a low risk of contamination and will remains available during summer. In Kelantan mainly on the northern part had taken best of this opportunity which turns this state into the largest groundwater abstraction in Malaysia. The groundwater abstraction activities started to increase when Kelantan river became high in contamination due to logging in the upper stream and uncontrolled sand mining which then forces the locals to find another alternative of freshwater sources. Subsequently, problems occur when some country in the world had suffered from land subsidence and seawater intrusion caused by over abstraction of groundwater in a particular area. To sustain the groundwater supply, understanding of the groundwater system is essential to develop proper groundwater management for future use. This research aims to investigate the sustainability of groundwater source at Northern Kota Bharu area for portable use. In the current situation, pumping activities at Kg Puteh, Pintu Geng and Tanjung Mas wellfield are running with a capacity of 37200m3/day, 9696 m3/day and 9875 m3/day. A suggestion has been made to increase the abstraction of groundwater at Tanjung Mas wellfield to 25375 m3/day which affect the current environment. Two-dimensional Electrical Resistivity method has been used to estimate the geological structure of the study area. 3 main layers has been identified in this study; sandy silt, gravelly sand and bedrock. with aids of resistivity and geological log, a groundwater model has been developed by using Visual MODFLOW software version 4.6 to evaluate the groundwater system at the study area. The model has been calibrated with r=0.802 and the calibrated groundwater model was then applied for prediction in normal and dry season. In this study, the prediction climate data were obtained from the Department of Irrigation and Drainage (DID). Groundwater recharge for the dry season was taking by 6% from the average annual rainfall while normal season is taking 18% of the average annual rainfall. The simulation result shows that groundwater source can be abstracted during normal condition with average recharge equal to 472.56 mm/year and total groundwater abstraction, of 9875 m3/day at Tanjung Mas wellfield without disturbing current pumping activities at Kg Puteh wellfield. In case of dry periods (recharge = 169.780mm/year), it can be seen the wide radius of influence, especially when increasing the pumping rate to 25375m3/day at Tanjung Mas wellfield. Tanjung Mas wellfield in scenario 4 has been taken to study the possibility for the subsidence to occur. Using Terzaghi’s consolidation theory, the total land subsidence can occur in this site is 0.035 meter if the water table drops for a long period. The calculation for 90% final subsidence for clay layers will take place after 21.8 years and this makes the subsidence rate at Tanjung Mas wellfield 1.47 mm per year. With the combination of population growth management, conservation strategies and augmentation of existing groundwater supplies, the groundwater model will become an important tool for sustainable groundwater development.